Efficacy of Nutritional and Psychosocial Interventions on Linear Growth and Neurodevelopment in Stunted Children in East Java, Indonesia: A Systematic Review and Meta-Analysis - Ananda Rizky (Archives of The Medicine and Case Reports, 2025)
Stunting remains a critical public health challenge in East Java, Indonesia, with profound implications for long-term health and capital development. While various interventions have been implemented, their consolidated effect on both physical growth and neurodevelopment is not well-established. This study aimed to synthesize the highest-quality evidence on the effectiveness of these programs. Following PRISMA 2020 guidelines, we conducted a systematic review and meta-analysis of studies evaluating stunting interventions in children under five in East Java, published between January 2015 and June 2025. We searched PubMed, Scopus, Web of Science, and Garuda databases. Included studies were randomized controlled trials (RCTs) and high-quality quasi-experimental studies reporting changes in Height-for-Age Z-score (HAZ) and/or standardized developmental outcomes. A random-effects model was used to pool effect sizes, reported as standardized mean differences (SMDs) with 95% confidence intervals (CIs). Of 1,824 articles identified, seven studies (n=2,985 children) met the stringent inclusion criteria. Interventions were categorized as nutrition-specific (n=2), nutrition-sensitive (n=2), and multi-component (n=3). Overall, interventions showed a significant positive effect on linear growth (SMD = 0.45; 95% CI [0.31, 0.59]; I²=68%). Subgroup analysis revealed that multi-component interventions combining nutritional support with psychosocial stimulation yielded a greater effect on HAZ (SMD = 0.61; 95% CI [0.42, 0.80]) than nutritional (SMD = 0.34; 95% CI [0.19, 0.49]) or psychosocial interventions alone. A significant, albeit smaller, effect was observed for developmental outcomes across four studies (SMD = 0.30; 95% CI [0.16, 0.44]). The pooled evidence from these core studies confirms that stunting interventions in East Java produce meaningful anthropometric improvements. The synergistic effect of combining nutrition with psychosocial support suggests that interventions must address not only nutrient deficits but also the behavioral and environmental factors that impair development. This dual approach likely mitigates the pathophysiological cycle of malnutrition, inflammation, and impaired cognitive development. In conclusion, multi-component stunting interventions appear to be most effective in East Java. Health policies should prioritize integrated programs that combine nutritional supplementation with responsive caregiving to maximize benefits for both physical growth and human potential.